VIBRATORY PARAMETERS OPTIMIZATION OF HARVESTER`S RUNNING GEAR SYSTEM - S.A. PARTKO (Advanced Engineering Research)
The article gives the analysis of possible criteria of application when accounting vibratory parameters mobile agricultural machines optimization. The example is given.